The Future of Logistics: A Literature Review of Digitalization Trends - Catalin-Alexandru VERDES; Alexandra-Andreea MIRONESCU (Communications of International Proceedings, 2023)
The aim of this study is to conduct a literature review on the impact of digitalization trends on logistics and its forthcoming developments. In order to perform the literature review, the PRISMA 2020 flowchart was used to select representative articles on this topic published in the Scopus database, aiming to identify emerging trends, challenges and opportunities in logistics. The analysis highlights the benefits of digitalization, such as process improvement, reduced costs, and improved customer service. The most important technologies used in the digitalization process are: internet of things, artificial intelligence, blockchain, robotics, and big data.
Keywords: logistics; digitalization; IoT